Sastra Profetik: Kajian Analisis Pemikiran Kuntowijoyo (Jurnal Adabiya, 2020)
Literary work is a process of creativity a person whose presence can not be separated from the reality of community life. Literary works present not only as an entertainment, but also bring enlightenment and soul-building tools. The values contained in a literary work are also related to the values of life and religious society. Thus, literature can contribute in shaping the values and strengthen the noble human character. These values are reflected in Kuntowijoyo’s thinking. This paper examines Kuntowijoyo’s thoughts relating to the idea of prophetic literature and how the form of Profetic literature he developed. The conclusion of this study is that prophetic literature developed by Kuntowijoyo is a literature of divine worth deriving from the values of the scriptures. It is a literature for believers. This prophetic literature is also referred to as literary worship, because it is an expression of appreciation of religious values. These values as a means of worshiping God. This can be seen from his prophetic meaning, namely the desire to imitate the Prophet’s attitude and attitude as a “Prophet”. This prophetic literature also contains human values, liberation and transcendence.
Keywords: Literature; profetic; Kuntowijoyo